Организация процесса учения путем аргументации – основной способ формирования навыков широкого спектра у младших школьников - Евсюкова, Т.А. (My University, 2016)
The article deals with the problems of modern education and possibilities of new approaches in formation of the lower grades pupils’ wide-ranging skills. As the main method of values and skills development, which has a priority in the updated educational program of Kazakhstan, the argumentation training is offered. The organization and implementation of the process of learning by argumentation has a positive impact on the formation of a wide range of skills: such as critical thinking, conduct research, the use of information and communication technologies, means of communication, including language skills.
Keywords: Education; State Compulsory Standard of Primary Education; Educational Content; WideRanging Skills; Expected Result; Argumentation; Requirements Assignment; Feedback